Employment Patterns, Poverty and Income Inequality. Issue 2 (May 2015) - Rani, Uma; Furrer, Marianne; Lavers, Tom
Abstract : The chapter looks at the impact of changing work patterns on poverty and income inequalities and discusses policy implications from the findings based on micro‐data from 40 countries. It finds that, on average, the standard form of employment is better remunerated than other types of work. Temporary and informal workers, part‐time workers and unpaid family workers, many of whom are women, are also disproportionately affected by poverty and social exclusion. Given the rise of non‐standard work forms and the increasing gap between the top and bottom, in many countries market income inequality has remained high or increased since the mid‐2000s. Despite this, some countries have been able to reduce poverty rates and disposable income inequality in the same time period, mainly by pursuing combinations of social protection and labour market policies.